Characteristicks of men, manners, opinions, times - Shaftesbury, Anthony Ashley Cooper of (Printed by John Baskerville, 1773)
I. Letter concerning enthusiasm. Sensus communis; an essay on the freedom of wit and humour. Soliloquy, or Advice to an autor.--II. Inquiry concerning virtue and merit. The moralist; a philosophical rhapsody.--III. Miscellaneous reflections on the preceding treatises and other critical subjects. A notion of the tablature, or judgment of Hercules.